Critical extension as a way to alleviate mutual ignorance (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
The article examines the problem of mutual ignorance among people, posed by W.E.B. DuBois as an “epochal tragedy” that hinders social emancipation. This phenomenon is a manifestation of a more general problem: the difficulty of emancipatory forces to conceive and fight for a freedom they do not fully know. The text suggests that critical university extension can be a key tool to confront this situation, since it promotes dialogue between academic and popular knowledge, facilitating the co-construction of knowledge. By creating these spaces for interaction, a more comprehensive understanding of social reality is favored. The experience of a Summer School of the Latin American Union of University Extension illustrates how these initiatives promote exchange and strengthen emancipatory projects by contributing to overcoming the problem of mutual ignorance.
Keywords: university extension; social change; open universities